Demands of People with Disabilities and Empowerment of Resilient Strategies - Delgado, Gustavo Rafael Escobar; Meza, Anicia Katherine Tarazona; ChÃƒÂ¡vez, Sandra Auxiliadora Romero; Murillo, Gabriela Stephanie AlcÃƒÂvar (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the research is to identify the resilient strategies in people with disabilities of the Technical University of ManabÃ. The paper presents a conceptual analysis associated with disability in university students. Some points of view related to the strategies of attention to diversity are exposed. A conceptual analysis related to resilience is provided. The situation of disabled students who are enrolled in the different careers of the Technical University of ManabÃ is addressed, specifying the type of disability they have. An analysis of the population is made for the study and the selection of the sample. The data related to the measurement of resilience is exposed to disabled students, for which the method developed by (Saavedra & Villalta, 2008) was used, consisting of 60 items, divided into 12 specific factors of resilience. Finally, a vision related to the resilience strategy demanded by disabled students of the Technical University of ManabÃ is offered.